Local overheating of transformers with high currents. Issue 2 (2nd March 2015) - Sitar, Robert; Janić, Žarko; Štih, Željko
Abstract : Purpose: – The purpose of the paper is to compare losses and temperatures in power transformer tanks for different high current lead arrangements. Design/methodology/approach: – 3D computational tools MagNet and ThermNet based on the finite element method are used to calculate magnetic field distribution in 3D models of power transformers. Eddy current losses in conducting metal parts are induced by the stray magnetic field of transformer windings and high current leads. From loss distribution and appropriate cooling condition temperature values are calculated. Findings: – From calculation results it is possible to understand advantages and disadvantages of different lead arrangements. The analysis is finalized with a short presentation of the influence of magnetic shielding height on temperature and loss values. Originality/value: – Results give transformer designer clearer understanding of precautions that should be taken for avoiding high temperatures on the tank wall of a transformer.